Answers

2014-07-04T16:55:18+08:00
(2x + 5y) + (3x – 2y) 
  =  2x + 5y + 3x – 2y
 
  =  2x + 3x + 5y – 2y
 
  =  
5x + 3y

(x3 + 3x2 + 5x – 4) – (3x3 – 8x2 – 5x + 6) 
  =  (x3 + 3x2 + 5x – 4) – 
1(3x3 – 8x2 – 5x + 6) 
  =  (x3 + 3x2 + 5x – 4) – 1(3x3) – 1 (–8x2) – 1(–5x) – 1(6) 
  =  x3 + 3x2 + 5x – 4 – 3x3 + 8x2 + 5x – 6
 
  =  x3 – 3x3 + 3x2 + 8x2 + 5x + 5x – 4 – 6
 
  =  
–2x3 + 11x2 + 10x –10
3 4 3
thank you!!!! it help me a lot!!!
  • Brainly User
2014-07-06T18:24:33+08:00
Subtraction Rule
 To subtract an expression from another expression, add it's negative. That is,
            a - b = a + (-b).

ex.
(5x + 4) - (7x +2)
(5x + 4) + (7x - 2)
(5x - 7x) + (4 - 2)
= -2x+2

HOPE IT HELPS
- KAI (;




1 4 1
thank you too!!! it will help me a lot too!!! ~~~suho ^_^ ~~~